ABYSSAL Database: an integrated WebGIS platform for deep-sea information from the South Atlantic - Gilberto Bergamo; Orlemir Carrerette; Bruno H. M. Souza; Thomás N. S. Banha; Paula D. Nagata; Paulo V. F. Corrêa; Arthur Z. Güth; Paulo Y. G. Sumida (Ocean and Coastal Research)
South Atlantic deep waters provide a huge diversity of habitats, with variations in areas such as geology, macrofauna, microbiology, physics, and chemistry. However, most of the data lacks central organization, important for subsequent deep-sea research, especially considering the multidisciplinary approaches and comparisons of the South Atlantic with other oceanic basins. Given the rising interest in commercial exploration off the deep-sea, especially with respect to hydrocarbon extraction and mining, there is an urgent need for a centralized repository of information with tools to collect and share geospatial data to support the conservation of this important oceanographic region. The main objective of this manuscript is to present an integrative database in WebGIS format for South Atlantic deep waters, open to further development in terms of data input, reliant on researcher collaboration, and with tools for ongoing maintenance and usability improvement driven by user feedback. The WebGIS format provides an open access, cost-free, feature-rich, and easy to use database through any Internet browser to reach the greatest number of researchers and students possible. The ABYSSAL database can be accessed at http://abyssal.io.usp.br.